(untitled) (Journal of the College of Basic Education, 2025)
 Build a training program according to the S.A.M.A.R. Samar model.  Measure the effectiveness of the program in developing teaching skills In order to achieve the second research objective, the researcher formulated the following null hypothesis: There is a statistically significant difference at a significance level of (0.05) between the performance of students in the experimental and control groups in post-teaching skills as measured by the observation card The research community consisted of fourth-stage students in the morning study at the College of Education / Al-Mustansiriyah University for the academic year (2023/2024), numbering (70) male and female students distributed into two sections. The researcher intentionally chose one of the two groups to be an experimental group trained according to the training program on S.A.A.M.A.R according to a model of (35) male and female students. As for the second group, it was a control group, and its members were (35) male and female students, who were trained according to the usual method. As for the researcher’s differences between the two groups in variables (chronological age in months, general average, Oates Intelligence Test, teaching methods subject score, pre-test scores), the researcher used the descriptive method to achieve the first goal of her research and the experimental method to achieve the second goal. The program consisted of (eight training sessions) and the researcher verified its validity by presenting it to a group of arbitrators.. As for the research tool, the researcher prepared an observation card, and they were distributed among the main teaching skills (planning, implementation, evaluation), and the researcher verified their validity and reliability, then applied them before and after on the research sample. The researcher trained the research sample during the experimental period, which began on Tuesday (10/10/2023) and ended on Tuesday (25/12/2024( To process the data statistically, the researcher used: SPSS package (, , Samir Nouf and Levin, and Pearson’s correlation coefficient) t test After analyzing the data, the researcher reached the following: There is a statistically significant difference at a significance level of (0.05) between the performance of the students of the experimental and control groups in the post-teaching skills as measured by the observation card The research results show that the students of the experimental group outperformed the students of the practical performance of teaching skills and the students of the control group failed. Thesis submitted by the student.